Linear maps preserving Pareto eigenvalues. Issue 5 (4th May 2017) - Alizadeh, R.; Shakeri, F.
Abstract : In this paper, we give the characterization of Pareto eigenvalues preserving linear maps on real square matrices. In fact, we show that a linear map on, the algebra of all n by n matrices with real entries, preserves Pareto eigenvalues if and only if, for some nonnegative generalized permutation matrix P .